Sensitivity of Commercially Available Influenza Rapid Diagnostic Tests in the 2018–2019 Influenza Season - Sakai-Tagawa, Yuko; Yamayoshi, Seiya; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2019)
Epidemics of seasonal influenza caused by H1N1pdm09, H3N2, and type B viruses occur throughout the world. Sporadic human H5 and H7N9 virus infections are also reported in particular regions. To treat influenza patients effectively with antivirals, sensitive and broad-reactive influenza rapid diagnostic tests (IRDTs) are required. Here, we tested the sensitivity of 23 IRDTs during the 2018–2019 influenza season for their ability to detect H1N1pdm09, H3N2, H5N1, H5N6, H7N9, and Victoria- and Yamagata-lineage type B viruses. All IRDTs detected all influenza A and B viruses tested but with different sensitivities. Several IRDTs detected the H5 and H7 viruses and the seasonal viruses with similar sensitivity. Such IRDTs might be useful for diagnosing patients infected with H5 and H7 viruses.